1999
DOI: 10.1093/carcin/20.4.669
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection enhances glandular stomach carcinogenesis in Mongolian gerbils treated with chemical carcinogens

Abstract: Helicobacter pylori (Hp) is thought to be a stomach carcinogen from epidemiological findings. To determine the effects of infection with the bacteria on experimental carcinogenesis, a study of the glandular stomach of Mongolian gerbils (MGs) was performed. Male MGs were treated with N-methyl-N'-nitro-N-nitrosoguanidine followed by inoculation with Hp or infected with Hp followed by N-methyl-N'-nitro-N-nitrosoguanidine administration. Animals were killed at week 50, and their excised stomachs underwent microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
127
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 47 publications
7
127
0
Order By: Relevance
“…23,25,30 Previous studies have documented that Hp-infected Mongolian gerbils develop intestinal metaplasia and can further progress to gastric cancer. 30 We have reported that SPEM associates human early gastric cancer more frequently than intestinal metaplasia and SPEM is also a gastric precancerous lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,25,30 Previous studies have documented that Hp-infected Mongolian gerbils develop intestinal metaplasia and can further progress to gastric cancer. 30 We have reported that SPEM associates human early gastric cancer more frequently than intestinal metaplasia and SPEM is also a gastric precancerous lesion.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] In addition, Hp infection promotes tumor development in the gerbil model. [23][24][25]27 While previous investigations have noted the presence of some intestinal metaplasia in gerbils, the role of SPEM in the genesis of gastric mucosal changes in gerbils is uncertain. In this study, we have examined the time course for metaplastic changes in fundic glands and the relationships between SPEM and goblet cell intestinal metaplasia in Hp-infected Mongolian gerbils.…”
mentioning
confidence: 99%
“…However, the overall, H. pylori antibody titers were lower, and in particular, they were significantly lower as compared with that in the low-intake group among the non-elderly (o65 years old) subjects. In general, higher H. pylori antibody titers correlate with more active H. pylorirelated CAG, as shown in clinical and animal studies (Eaton and Krakowka, 1992;Shimizu et al, 1999;Loffeld et al, 2000;Nozaki et al, 2002). In particular, in H. pylori-infected Mongolian gerbils, higher antibody titers are associated not only with more active gastritis, but also with a higher incidence of gastric cancer (Shimizu et al, 1999).…”
Section: Discussionmentioning
confidence: 65%
“…In general, higher H. pylori antibody titers correlate with more active H. pylorirelated CAG, as shown in clinical and animal studies (Eaton and Krakowka, 1992;Shimizu et al, 1999;Loffeld et al, 2000;Nozaki et al, 2002). In particular, in H. pylori-infected Mongolian gerbils, higher antibody titers are associated not only with more active gastritis, but also with a higher incidence of gastric cancer (Shimizu et al, 1999). In light of these previous findings, our results suggest that although JA intake does not eradicate established H. pylori infection from the gastric mucosa, it may, by virtue of a direct bactericidal action on H. pylori and anti-inflammatory effects, decrease the severity of gastritis.…”
Section: Discussionmentioning
confidence: 65%
“…Metaplasia may then progress to gastric cancer, especially to tumors that are intestinal (52). Recently, Shimizu et al conducted a carcinogenesis experiment by infecting Mongolian gerbils with H. pylori and reported that progression to gastric cancer was chiefly seen in animals that showed a high H. pylori antibody titer (59). To consider the association between H. pylori infection and the onset of diffuse type of gastric cancer, the process from infection with H. pylori through gastric mucosal atrophy, intestinal metaplasia, and developmentof cancer must be ex- As has been discussed, there is little doubt that persistent infection with H. pylori is closely related to the development of gastric cancer.…”
Section: Gastric Cancermentioning
confidence: 99%